Oxford Junior Thesaurus - Compiled by Dignen, Sheila (New York Oxford University Press, 2012)
The Oxford Junior Thesaurus is ideal for the KS2 curriculum, with thousands of synonyms, age-appropriate example sentences, and extra writing help with tips for overused words, for writing stories, and even for text messaging. It is easy to use with its clear layout, and the full alphabet with tabs on every page.
Keywords: Dignen, Sheila